The Relationship between Parents' Smoking Behaviour and the Incidence of Acute Respiratory Infections in Toddlers at the Southeast Sulawesi Police Primary Clinic - Sitti Herliyanti Rambu; Mirasantika Mirasantika; Asmiana Saputri Ilyas (CV. Global Health Publication, 2025)
Acute Respiratory Infection (ARI) is one of the most common diseases in toddlers and is the leading cause of morbidity and mortality worldwide. One of the factors that contributes to the high incidence of ISPA in toddlers is exposure to cigarette smoke from parents or family members who smoke in the house. Based on the report of the South Sulawesi Police Primary Clinic, cases of ISPA in toddlers have continued to increase in the last three years, so research is needed on factors related to this incident. Objective: To determine the relationship between parental smoking behaviour and the incidence rate of ISPA in toddlers at the South Sulawesi Police Primary Clinic in 2025. Methods: This study is an observational analytical research with a cross-sectional design. The sample amounted to 46 respondents who were selected using the simple random sampling technique. Data collection was conducted using questionnaires, and data analysis was carried out using univariate and bivariate methods using the Chi-Square test with a significance level of 0.05. Results: The results showed that out of 46 toddlers, as many as 41 toddlers (89.1%) experienced ISPA. Parental smoking behaviour was found in 29 people (63.0%). The results of the Chi-Square test showed a value of p = 0.035, which means that there is a significant relationship between parental smoking behaviour and the incidence of ISPA in toddlers. Conclusion: The results of this study confirm the importance of efforts to prevent exposure to secondhand smoke in toddlers through increasing parental awareness about the impact of smoking behaviour on children's health. These findings can be the basis for health workers to strengthen health education, smoking cessation counselling, and the implementation of smoke-free home policies to reduce the incidence of ISPA in children under five. In addition, the results of this study are expected to be considered in the planning of promotive and preventive programs in health service facilities, especially in the Southeast Sulawesi region.